ANALISIS PENGARUH LABA BERSIH, ARUS KAS OPERASI DAN STRUKTUR MODAL TERHADAP DIVIDEN KAS PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Rahayu, Sri; Yudha PP, Irvan (Accounting Research and Business Journal, 2023)
ABSTRACT This study aims to examine the effect of Net Profit, Operating Cash Flow and Capital Structure on Cash Dividends in Primary Consumer Goods Sector companies for the 2017-2021 period. The sampling technique used in this study was a purposive sampling technique. The research hypothesis testing method uses multiple linear regression analysis and the classical assumption test. The data source used in this study is secondary data obtained from the Indonesia Stock Exchange (IDX). The dependent variable in this study is Cash Dividend while the independent variables in this study are Net Income, Operating Cash Flow and Capital Structure. The results of multiple linear regression analysis found the equation Y = -2.036 + 0.155X1 + 0.002X2 + 0.130X3. The results of the t test (partial) Operating Cash Flow has no significant effect on Cash Dividends. While Net Income and Capital Structure Have a Significant Influence on Cash Dividends. The results of the F test (simultaneous) Net Profit, Operating Cash Flow and Capital Structure simultaneously have a Significant Effect on Cash Dividends with Fcount 4.011 > Ftable where the Ftable value obtained from n = 35 and K = 3 is 2.91 and a significant value of 0.016 < 0.05